A Comparison of Capital and Labor Incomes in Finance and Manufacturing Sectors in OECD Countries: 1995–2019. (21st April 2023) - Koç, Abdilcelil
Abstract : Using data from 31 OECD countries, this study analyzes labor and capital incomes in the international manufacturing and finance sectors during the years 1995 to 2019. The study examines three periods: the years between 1995 and 2007, before the global crisis; between 2008 and 2019, during and after the global crisis; and the 1995–2019 period overall. In addition, the variables were subjected to general trend analysis, to analysis of the relative change between the beginnings and ends of the various periods, and to analysis of the annual average percentage changes. The results show that in both the manufacturing and financial sectors, the incomes of capital increased more than those of labor. Comparing the two sectors, it can be stated that between 1995 and 2019 the degree of class inequality in favor of capital saw a greater increase in the sector of manufacturing industry.